Effectiveness of thin surface treatment in Kansas - Rahman, Md. Shaidur (Kansas State University, 2010)
Preventive maintenance strategies are applied to pavement to bring it back to appropriate serviceability when it starts to deteriorate soon after construction due to several factors, e.g., traffic loading, deterioration of pavement materials, and climatic effects. In recent years, more and more highway agencies are adopting preventive maintenance strategies and moving away from rehabilitation actions since rehabilitating pavements at near failure is not a cost-effective pavement management technique. A variety of preventive maintenance treatments or thin surface treatments are available to bring pavements back to appropriate serviceability for road users. The Kansas Department of Transportation (KDOT) has adopted several preventive maintenance treatments including thin overlay, ultra-thin bonded asphalt surface (Nova Chip), chip seal, and slurry seal. This thesis discusses the effectiveness of thin surface or preventive maintenance treatments applied in 2007 on 16 highway sections in Kansas. Three types of thin surface treatments, 25-mm Hot-Mix-Asphalt (1” HMA) overlay, ultra-thin bonded asphalt surface (Nova Chip), and chip seal, were examined in this study. These treatments were applied on three types of surface preparation, namely, bare surface, 25-mm surface recycle (1” SR), and 50-mm surface recycle (2” SR). Effectiveness of the thin surface or preventive maintenance treatments for mitigating typical distresses and enhancing pavement performance was evaluated by conducting before-and-after (BAA) comparisons. All data required for this study were extracted from the Pavement Management Information System (PMIS) database of KDOT. It was observed that transverse and fatigue cracking significantly decreased and rutting conditions were improved after the thin surface treatments were applied. Roughness conditions were observed to be better on the highway test sections treated with 25-mm (1”) HMA and Nova Chip, while the effects of chip seals on reducing roughness were not as obvious. Benefit and performance levels of the pavements were observed to rise after the thin surface treatments were applied. The Hamburg Wheel-Tracking Device (HWTD) test was conducted on core samples taken from the highway sections under this study. Laboratory test results showed that most projects exceeded the maximum rut-depth limit (20 mm) specified for 20,000 wheel passes, and the number of wheel passes to failure varied significantly among the projects. Cores from only three projects, two treated with Nova Chip and one with 25-mm (1”) HMA, carried 20,000 wheel passes without exceeding the maximum rut limit of 20 mm (0.8 inch). Pair-wise comparisons or contrasts among the treatments were also performed with the statistical analysis software, SAS. Air void of the HWTD test cores was found to be a significant factor affecting performance of thin surface treatments. The results also revealed that performance was significantly affected by the type of treatment and surface preparation.
Keywords: Thin surface treatment; HMA overlay; Nova Chip; Chip seal; PMIS; Hamburg rut tester; Engineering, Civil (0543); Transportation (0709)